Determination of Distribution of Ozone Content in Lower Troposphere and Atmospheric Aerosol Optical Thickness over Territory of Georgia Using Satellite Data and Ground Truth Measurements - Stankevich, Sergey A.; Titarenko, Olga V.; Amiranashvili, Avtandil G.; Chargazia, Khatuna Z. (Journals of Georgian Geophysical Society, 2015)
Aerosol and ozone are very important parameters of the atmosphere. The data of these small constituents are required for the simulation of atmospheric processes, weather forecasting, study of climate variation, ecological appraisals and, etc. In the majority of studies is necessary the information above the large regions or continents. Ground-based study of these atmospheric parameters over the large area is difficult and expensive procedure. Furthermore, large changeability in the environment requires the rapid renovation of measurements. This circumstance requires the creation of the dense network of the ground stations of observations. At present in the world there are several satellite systems for the operational global checking of the atmospheric parameters. These satellites are equipped with microwave and optical instruments for measuring the atmospheric parameters, such as the aerosol optical thickness of the atmosphere, the content of water vapor, ozone, greenhouse gases, carbon monoxide, nitrogen, sulfur, profiles of temperature, pressure and relative humidity, cloudiness and etc. The relatively low accuracy of satellite measurements can be considerably improved by correction with the data of ground-based measurements. Work examines the methodology of the determination of the distribution of the ozone content in the lower troposphere and the aerosol optical thicknesses of the atmosphere above the territory of Georgia according to the data of satellite and ground-based measurements in Tbilisi. For an example the schematic pictures of the 3D distributions of the ozone in the 2.5- km layer of the atmosphere, and also the aerosol optical thickness of the atmosphere above the territory of Georgia and contiguous countries for all days of observations, and also cloudless and not much cloud days are given.